The nutritional quality of captive sambar deer (Rusa unicolor brookei Hose, 1893) velvet antler - GONO SEMIADI; YULIASRI JAMAL (Society for Indonesian Biodiversity, 2015)
Semiadi G, Jamal Y. 2015. The nutritional quality of captive sambar deer (Rusa unicolor brookei Hose, 1893) velvet antler. Biodiversitas 16: 156-160. Deer farming has been a well-developed agriculture diversification worldwide since 1970s. To the presenttime information concerning the nutrient value of velvet antler of sambar deer (Rusa unicolor brookei Hose, 1893) is limited. Therefore,a study on the nutritional quality of velvet antler of captive sambar deer was conducted. Velvet antlers were obtained from captivesambar deer in Penajam Paser Utara, East Kalimantan, Indonesia, and were analyzed for its nutritional quality from the hard and softparts. The results showed that fresh weight of a pair of velvet antler (approx. 70 days post hard antler cast) was 523.1 g (SE = 49.99). Inthe soft part of the velvet antler, ash content was 25.9% DM (SE= 0.78) as compared to 40.4% DM (SE = 1.07) in hard part, whilst thelipid and protein contents from the soft part were 3.3% DM (SE = 0.20) and 70.8% DM (SE = 2.07), respectively, higher compared tothose in the hard part being 1.9% DM (SE = 0.12) and 59.5% DM (SE = 1.92), respectively. From the study it can be concluded that theproduction of velvet antler from captive sambar deer seemed to be far from its genetic potency, and the nutritional qualities of the velvetantler contents were not different from the red deer Cervus elaphus.